Using Functional Grammar Teaching to Improve Analytical Exposition Text Writing for senior high school students in Karanganyar - Aulia Zulfa Indi Putri; Sujito (VISA: Journal of Vision and Ideas, 2024)
Functional grammar is a type of grammar discovered by Michael Halliday in the 60s. Even though this feels foreign to foreign language teachers at school, it is very interesting for scientific developers. In the field of language education, functional grammar is more commonly applied in terms of speaking and writing. The background to this is because functional grammar has an important purpose for foreign language students and provides facilities for foreign language students to know the language knowledge they need to know to be successful in school. This research hopes that researchers can find out whether there is a positive influence on the level of success of functional grammar knowledge in writing expository analytical texts during the second semester of the second year of SMA Muhammadiyah 1 Karanganyar. This research uses a quantitative design. Researchers used pretest and posttest to determine the effectiveness of the treatment used in this study. The final design is to determine the influence between research variables. The T test results show a sign (two-tailed) of 0.000 and a significance level of 0.05. The result is Sig. (two-tailed) is below the significance level, so the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that students who are given material using functional grammar are more able to write analytical and expository texts than students who are not given functional grammar. It can be interpreted that functional grammar has a very good influence in writing expository analytical texts. Functional grammar can be used to support writing analytical descriptive text. Students will be able to develop writing skills, especially expository analytical writing. This grammar can also make students more critical when creating analytical descriptive texts.